Influence of Aerodynamic Abrasive Treatment on the Phase State of the Surface Layer of Ceramics of Partially Stabilized Zirconium Dioxide; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 15, iss. 3 - Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (2021, 2021)
Title screen